EMPLOYEE UPBJJ-UT PERCEPTIONS OF THE ROLE AUDITOR INTERNAL AUDIT - Any Meilani; Yeni Widiastuti (Conference In Business, Accounting, And Management (CBAM), 2015)
Differences in employee perceptions of the role of internal auditors can not be avoided. It is natural to happen because the perception is influenced by many factors. In performing its duties, the auditor can act as a supervisor, consultant and catalyst. The research objective was to obtain a Auditor Internal Audit (SPI) auditor's role in conducting the audit. The population in this study were employees Unit Distance Learning Courses Open University (UPBJJ-UT) throughout Indonesia. Samples were taken by simple random sampling 234 employees. Data collected by distributing questionnaires directly or indirectly to employees. The data were analyzed using descriptive statistical analysis and comparative analysis. The results showed that: (1) The role of the Auditor SPI as a consultant rank 1 (mean = 3.15). This suggests that employees UPBJJ-UT requires internal auditors not only focused on the discovery of fraud, but also act as an internal consultant; (2) The role of the auditor SPI as supervisors (mean = 3.10) was ranked second, meaning that the role of the auditor run the SPI still adhered to the old paradigm, advice and recommendations provided only short-term; (3) The role of the auditor SPI as a catalyst (mean = 3.06) was ranked third, meaning that this role is the role played by the auditor at least SPI. In applying this role fully takes time and a lo ng process, because the auditor's role as a catalyst SPI is dependent upon the quality of the auditor and the support and commitment of the leadership of the UT. Keywords: perception, auditors, supervisor, consultants, catalyst